Abnormal extant xiphosurids in the Yale Peabody Museum Invertebrate Zoology Collection - Bicknell, R; Pates, S (Yale Peabody Museum of Natural History, 2019)
Xiphosurids are an archetypal group of chelicerates with extensive anatomical, physiological, and paleontological documentation. Despite this research, very little information is available concerning abnormal specimens of the group. Here we vastly increase the number of documented abnormal extant xiphosurids by identifying 17 specimens showing a range of abnormalities on the appendages, cephalothorax, thoracetron, and telson. These specimens include all extant species and the first documentation of abnormal Carcinoscorpius rotundicauda. We note that previous suggestions that the telson was the most commonly abnormal body part may reflect a speciesspecific bias and propose increased use of museum collections to understand these iconic organisms and their abnormalities.